THE CONTRIBUTION OF MORPHOLOGY TO THE QUANTITATIVE POTENTIAL OF NICKEL LATERITE DEPOSITS HIGHLY WEATHERED ULTRAMAFIC ROCKS IN THE SOUTHEAST ARM REGION OF SULAWESI ISLAND, INDONESIA - Pachri, Hendra; Imran, A M; Hizbullah, Izza (Badan Geologi, 2024)
ABSTRACTThe research locations include Pomalaa in Kolaka Regency, Southeast Sulawesi, and Sorowako in East Luwu Regency, South Sulawesi. This study primarily aims to examine the comparative impact of morphology on the distribution of nickel ore enrichment zones and nickel ore thickness within laterite deposits in Southeast Sulawesi, specifically contrasting Pomalaa and Sorowako. The research was conducted in multiple phases: preparation (including planning for costs, timelines, and permits), data collection (which covers both field and laboratory analyses for material properties and geological information), data analysis (which involves laboratory tests utilizing XRF, petrographic studies, slope morphology evaluations, and profiles of lateritic nickel deposits), representation of morphology features in graphical format, and finally, compiling a scientific report based on the data analyses and interpretations. The relationship between characteristics of laterite profiles and morphology indicates that the steepness of slopes impacts water drainage and the lateralization process, with certain morphologies displaying superior thickness than others. Moreover, the thickness observed at some boreholes is affected not only by morphology but also by structural aspects, as indicated by favorable Rock Quality Designation (RQD) values. This study has mainly highlighted the effects of morphology and zone thickness on the nickel concentration found in laterite deposits. Therefore, it is suggested that further research should investigate additional factors, such as the structural properties of nickel laterite deposits.Kata kunci: Bedrock, Morphology, Nickel Laterite, Rock Quality Designation (RQD)ABSTRAKLokasi penelitian meliputi Pomalaa di Kabupaten Kolaka, Sulawesi Tenggara, dan Sorowako di Kabupaten Luwu Timur, Sulawesi Selatan. Penelitian ini bertujuan untuk mengkaji dampak perbandingan morfologi terhadap sebaran zona pengayaan bijih nikel dan ketebalan bijih nikel dalam endapan laterit di Sulawesi Tenggara, khususnya membandingkan Pomalaa dan Sorowako. Penelitian dilakukan dalam beberapa tahap: persiapan (termasuk perencanaan biaya, jadwal, dan izin), pengumpulan data (yang mencakup analisis lapangan dan laboratorium untuk sifat material dan informasi geologi), analisis data (yang melibatkan uji laboratorium menggunakan XRF, studi petrografi, evaluasi morfologi lereng, dan profil endapan nikel laterit), representasi fitur morfologi dalam format grafis, dan akhirnya, menyusun laporan ilmiah berdasarkan analisis dan interpretasi data. Hubungan antara karakteristik profil laterit dan morfologi menunjukkan bahwa kecuraman lereng memengaruhi drainase air dan proses lateralisasi, dengan morfologi tertentu menunjukkan ketebalan yang lebih unggul daripada yang lain. Selain itu, ketebalan yang diamati di beberapa lubang bor tidak hanya dipengaruhi oleh morfologi tetapi juga oleh aspek struktural, seperti yang ditunjukkan oleh nilai Rock Quality Designation (RQD) yang baik. Studi ini terutama menyoroti efek morfologi dan ketebalan zona pada konsentrasi nikel yang ditemukan dalam endapan laterit. Oleh karena itu, disarankan agar penelitian lebih lanjut menyelidiki faktor-faktor tambahan, seperti sifat struktural endapan laterit nikel.Keywords: Batuan dasar, Morfologi, Laterit Nikel, Rock Quality Designation (RQD)